Fiber Laminate Adding Effect to Tensile Strength, Hardness, and Fault Surface of Teki Grass (Cyperus Rotundus) Composite - Rafiq Yanhar, Muhammad; R Harahap, Muksin; Bachori, Ahmad; Napid, Suhardi; Sri Poneni, Istu; Hasibuan, Abdurrozzaq (International Journal of Engineering and Technology, 2018)
The aim of this research is to know the fiber laminate adding effect to tensile strength, SEM photo, and hardness of teki grass (cyperus rotundus) composite specimen. Tensile and hardness test specimens were prepared by hand lay-up method with variations of 1, 2, and 3 fiber layers. Test results showed the highest tensile strength occurred in 1 layer fiber of 21.83 MPa and decreased in 2 layers of fiber and 3 layers of fiber of 17.95 MPa and 16.17 MPa. This is caused by random fibers that spread in all directions so that many fibers are not aligned with the tensile force. Addition of the fiber layer results in reduced resin volume so that the bond between fiber and matrix also decreases, which in turn will make the fiber cannot withstand tensile well. Analysis of SEM photographs also proves that the reduced volume of resin causes the bond between fiber and matrix to decrease resulting in cavities in 2 layer and 3 layers of composite. The results of the hardness test show that the addition of fiber layer decreases the hardness value. This is due to the soft grass fiber that is softer than the resin polyester, so that the added layer of fiber will reduce the hardness value.
Keywords: Fiber laminate; Tensile Strength; Hardness; Fault surface; Teki Srass Composite